Tinjauan Ekonomi Islam terhadap Pembulatan Harga pada Usaha Jasa Laundry Alami Kota Parepare - Salsabila, Mayza; Saharani; Umaima (Balanca : Jurnal Ekonomi dan Bisnis Islam, 2021)
Service businesses that are in great demand by the community in their daily needs are lodging rental services, laundry or laundry services, computer repair services, motorcycle repair services, photography services, educational services and many other services. One of them is a laundry service which has also begun to be widely established, including in the city of Parepare. laundry service providers in weighing clothes using digital scales so that they are able to display the weight and price to be paid. However, in practice there is rounding of prices which will then be analyzed in the perspective of Islamic business ethics.